Impfstoffe gegen Meningokokken für das Kindesalter = Vaccines against meningococci for children - Tenenbaum, Tobias; Hellenbrand, Wiebke; Schroten, Horst (Monatsschrift Kinderheilkunde, 2019)
Currently, the German Standing Committee on Vaccination of the Robert Koch Institute (STIKO) recommends vaccination against meningococci of serogroups A, B, W and Y only for risk groups. In contrast, vaccination against meningococci of serogroup C is recommended for all children in the first year of life. There are two recombinant protein meningococcal B (MenB) vaccines, the 4‑component vaccine 4CMenB and a 2-component vaccine including 2 variants of the factor H binding protein (fHbp; rLP2086) that are also licensed in Germany. The coverage of the circulating MenB strains of the two vaccines is approximately 80%. The 4CMenB vaccine is licensed for all age groups whereas the fHbp vaccine is licensed only for adolescents and adults. The potential universal implementation of MenB vaccines in children will be further evaluated by the STIKO in the context of the epidemiological situation and as data on long-term vaccine effectiveness and safety and effects on carriage become available.
Gesehen am 30.04.2019